2019
DOI: 10.1108/et-07-2018-0154
|View full text |Cite
|
Sign up to set email alerts
|

Graduate readiness for the employment market of the 4th industrial revolution

Abstract: Purpose The purpose of this paper is, first, to examine student perspectives of their university experience in terms of the soft employability skills they develop; second, how prepared those students feel for the future employment market and finally investigate whether there are differences in perceptions between Chinese and Malaysian students given their different educational experience. Design/methodology/approach In this study, 361 predominantly Chinese undergraduate students at two universities, one in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 37 publications
7
131
0
8
Order By: Relevance
“…The practical importance of this study is twofold: first to increase awareness among educational managers and employees of the importance of soft skills and second to reveal and assess the degree of any discrepancy in employer and employee perceptions. This paper empirically confirms the prevailing perception concerning the phenomenon of the "skills gap," which has been widely discussed in the academic literature (Stapleton, 2017;Teng et al, 2019;Chan, 2015). An identified gap could motivate further research on the causes of the gap and the ways it can be addressed.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…The practical importance of this study is twofold: first to increase awareness among educational managers and employees of the importance of soft skills and second to reveal and assess the degree of any discrepancy in employer and employee perceptions. This paper empirically confirms the prevailing perception concerning the phenomenon of the "skills gap," which has been widely discussed in the academic literature (Stapleton, 2017;Teng et al, 2019;Chan, 2015). An identified gap could motivate further research on the causes of the gap and the ways it can be addressed.…”
Section: Introductionsupporting
confidence: 87%
“…Recently Succi and Canovi (2019) found that the large majority of employers (60.2%) agreed that students are not well or very well prepared by higher education institutions. The differences highlighted could help education units to reconsider the importance of soft skills and include them in their curricula, leading to the acquirement of skills in levels, closer to employers' standards (Teng et al, 2019).…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%
“…Moreover, employers are concerned with the shortage of employability skills, already demonstrated by the entry-level job applicants as this is considered a global issue (Teng et al, 2019). Despite employability importance, there are discrepancies in the visions on employability skills between higher education students and employers (Kőnig et al, 2016;Ahmad & Pesch, 2017;Singh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent articles on education in industrial revolution 4.0 tackle the integration of technology into learning process. The discussion relates to the use of Artificial Intelligence (AI), augmented and virtual reality, which can trigger creativity and pleasure in learning (Buasuwan, 2018;Shahroom & Hussin, 2018;Teng et al, 2019). I think that integrating information technology with edu cation is less significant compared to the values-transfer function in education.…”
Section: Figure 3 Accountants and Ethics Are Not Synchronizedmentioning
confidence: 99%